(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
A new Schiff base ligand N-(2-fluorobenzylidene) isonicotinohydrazone (LH)and its coordination complexes of Cu(II), Co(II) and Zn(II) were synthesized. Elemental investigations, melting point determination, molecular weight determination, IR, 1H-NMR, Mass Spectrometry and UV spectrum studies were used to describe the structure and bonding pattern of ligand and their metal complexes. The above-mentioned analysis revealed that the ligand coordinates to the metal atom in a bidentate manner and an octahedral geometry for Co(II) complexes, a square planer geometry for Cu(II) complexes and a tetrahedral geometry for Zn(II) complexes have been proposed. The antibacterial activity of the compounds was screened against E. coli and B. subtilis, as well as antifungal activities like P. Chrysogenum and A. Niger to assess the antimicrobial potential of all complexes. The results of antimicrobial activity indicate that the metal complexes exhibit superior antimicrobial activity than the ligand. The antioxidant and anti-diabetic activities of the ligand and its metal complexes were also tested and they are found to possess considerable antioxidant andanti-diabetic characteristics. The antioxidant activity shown by metal complexes is better than parent ligand and metal salts. The best alpha-amylase inhibitory activity was observed for the Cu(II) complex with the lowest IC50 value.